From Participation to Consumption: The Role of Self-Concept in Creating Shared Values Among Sport Consumers - Wu J; Wu Y (Psychology Research and Behavior Management, 2023)
Ji Wu,1,2 Yigang Wu3 1School of Economics and Management, Shanghai University of Sport, Shanghai, 200433, People’s Republic of China; 2School of Kinesiology, College of Education and Human Development, University of Minnesota, Minneapolis, MN, USA; 3School of Physical Education, Shanghai University of Sport, Shanghai, 200433, People’s Republic of ChinaCorrespondence: Yigang Wu, Tel +86-15618991089, Email wuyigan08@sus.edu.cnIntroduction: The contribution of sport organizations to solving social issues has been acknowledged. However, little is known about how sport organizations can turn social issues into business opportunities as a means of creating shared value (CSV). Building on self-concept theory, a framework was established to examine how sport organizations can promote sport participation and simultaneously drive sport consumption—as a means of CSV—by enhancing consumers’ sport self-concept.Methods: A total of 311 participants recruited from a CSV program delivered by a sport organization completed a time-lagged survey. Structural equation modeling was performed with Mplus 8.3 to test the framework.Results: The results revealed that consumers’ sport self-concept was enhanced by their perceptions of sincere interest from employees of the sport organization, while effect of their perceptions of praising was insignificant. Sport self-concept has a positive association with their levels of sport participation and simultaneously influences their intention to purchase the sport organization’s products due to self-congruity.Discussion: This study contributes to CSV literature by demonstrating the role of sport self-concept in CSV in a sport setting. Our findings suggest that sport organizations might focus on strengthening consumers’ sport self-concept to create both social and economic value through their CSV.Keywords: shared value creation, sport self-concept, sport marketing, social value, economic value